Switching roles : an investigation into the use of reverse-mentoring by students to encourage teachers' uptake of ICT in their pedagogical approach - Peterson, Michael Joseph (Curtin University, 2012)
The literature provided evidence that the integration of teaching and learning with ICT was critical to support learner centred pedagogies. There was also clear evidence that a number of key barriers were impacting on the ability of teachers to integrate ICT in their classrooms. These barriers include teachers' perceptions of the lack of usefulness of the technologies and a lack of knowledge of how to use the technologies. The literature also noted that female teachers were less likely than their male colleagues to take up ICT in their teaching—the so called gender barrier. Teachers are adult learners and have special needs associated with adult learning such as the need for individual and personalised learning programmes delivered at a time of their choosing. One approach to meet those special needs and overcome barriers preventing the uptake of ICT was through reverse-mentoring which is the use of students to help teachers with ICT issues in a timely and relevant manner.The benefits of reverse-mentoring have not been widely explored in the literature and this study provided evidence that the programme delivered both timely and relevant professional development for the participant teachers. Also the concept of students helping their teachers to develop skills with ICT fitted well with constructivist learning theory and this helped overcome many of the barriers associated with adult learning. The research design employed mixed methods multiple case studies which provided complementary lenses through which quantitative and qualitative data were assessed. The data analysis was complemented through the use of Activity Theory. The research also investigated the extent the reverse-mentored programme assisted female teachers' uptake of ICT in their teaching.